A evoluç\~ao da estrutura tributária e do fisco brasileiro: 1889-2009 - Fabrício Augusto de Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This work analyses the evolution of the tributary structure and the constitution and organisation of the Brazilian revenue system in the long period from 1889 to 2009. It aims to identify, on one hand, the functions attributed to fiscal policy and to taxation, as well as how these State`s intervening instruments were - and are - developed to achieve their role, under the perspective of numerous theoric and prevailing conceptions concerning this role; on the other hand, how the taxation apparatus, during this scenery change, developed and behaved to provide the essential resources to the performance of its functions. It concludes that whereas the tributary system, after being modernised in the decade of 1960, has retroceded after the Brazilian Constitution (1988), process that was exasperated during the two following decades as an outcome from the compromises accepted with the formation of elevated primary surpluses, the revenue system treaded to a different direction, causing a true modernising revolution in its apparatus, capacitating itself to collect, more efficiently, the taxes in the country.
Keywords: H20; 330; Finanzpolitik; Steuersystem; Öffentliche Einnahmen; Brasilien